EDUKASI TENTANG PROSEDUR PERMINTAAN RUJUKAN BPJS DI PUSKESMAS TALUN KENAS - Jon Piter Sinaga; Sri Sudewi Sitio (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Talun Kenas Health Center is one of the Technical Implementation Units of the Deli Serdang District Health Office. In the current BPJS era, the Talun Kenas Health Center provides first-level health services related to the National Health Insurance, where referrals for BPJS patient services are still said to be high from 2017. This is caused by officers who do not understand the referral policy for outpatient health centers properly, the availability of medicines is limited and the supporting facilities for medical equipment are minimal. Education is carried out with the aim that officers who are responsible for and involved with BPJS referral procedures can carry out their duties better due to increased knowledge and understanding of the BPJS referral system. The number of participants in the educational activity was 18 health workers at the Talun Kenas Health Center. After the implementation of the activity, there was a significant increase in knowledge related to the referral system and referral for BPJS patients.